Global Citizens – Global Jet Setters? The Relation Between Global Identity, Sufficiency Orientation, Travelling, and a Socio-Ecological Transformation of the Mobility System - Loy, Laura S.; Tröger, Josephine; Prior, Paula; Reese, Gerhard (Frontiers in Psychology, 2021)
Global crises such as the climate crisis require fast concerted action, but individual and structural barriers prevent a socio-ecological transformation in crucial areas such as the mobility sector. An identification with people all over the world (i.e., global identity) and an openness towards less consumption (i.e., sufficiency orientation) may represent psychological drivers of a socio-ecological transformation. We examined the compatibility of both concepts as well as their relation to people’s support of a decarbonised mobility system and their flight mobility behaviour – a CO2-intensive behaviour that may be particularly difficult to refrain from for globally identified people, but less so for sufficiency-oriented people. In an online study conducted in Germany (N = 317), we found that global identity and sufficiency orientation were positively related. Both were negatively related to past flight-related CO2 emissions and positively related to refraining from flying and the support of decarbonised mobility policies. Accounting for both showed that sufficiency orientation in particular was related to fewer flight-related CO2 emissions and refraining from flying. Furthermore, we examined people’s travel experiences. While global identity was unrelated to the frequency and duration of international travelling, it was positively related to the frequency and quality of contact with local people met on journeys. An experimental variation of whether participants first answered questions on global identity or on travel experiences revealed that remembering past international travelling led to higher reported levels of global identity. Taken together, global identity seems to profit from in-depth international contact with people, but can be decoupled from resource-intensive travel behaviour. Globally identified and sufficiency-oriented people may support a socio-ecological transformation. Our results indicate a compatibility of global identity and sufficiency orientation. Experimental and longitudinal research should examine causal links to foster our understanding of the conditions under which both can be strengthened.